ANALISIS PERILAKU KEUANGAN KELUARGA MUDA KELAS MENENGAH DI INDONESIA (STUDI KUALITATIF BERDASARKAN PERSPEKTIF PERILAKU KEUANGAN RUMAH TANGGA DAN TEORI PERILAKU TERENCANA) - Abdul Hafiz; Siti Napisah; Berandi Suaryansyah (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The purpose of this study is to explore the financial behavior of middle-class urban families in Indonesia. This study use Behavioral Household Finance framework and integrated it with Theory of Planned Behavior. Despite the increaseing of financial literacy, many households have poor financial behaviors. Using a qualitative approach, the research gets insights from in-depth interviews with nine families selected through purposive sampling. Participants were middle-income family living in urban areas with school-aged children. Thematic analysis revealed that financial behavior is shaped by cognitive biases, social norms, perceived behavioral control, and financial literacy. Limited financial knowledge and negative perceptions of formal financial institutions also hindered their ability to improve their financial behavior which represented in their financial outcome. On the other hand, families with higher financial literacy demonstrated better control over their finances, proactive saving strategies, and more resilience against behavioral biases and social pressure. These findings highlight that enhancing financial literacy alone is insufficient without addressing the psychological and cultural factors that influence financial decision-making. This study offers implications for the design of financial education and policy interventions that go beyond technical knowledge and incorporate behavioral insights aligned with local cultural values.